PERANCANGAN SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PEMBUANGAN SAMPAH LEGAL PADA DINAS KEBERSIHAN DAN PERTAMANAN KOTA LUBUKLINGGAU BERBASIS WEB MOBILE - Elmayati Elmayati; Cindi Wulandari Wulandari; Hendra Saputra Saputra (Jurnal TAM (Technology Acceptance Model), 2018)
Department of Hygiene and Gardening in Lubuklinggau has given the information about the location of waste disposal legal still in conventional data. It resulted in the map less provide complete information and difficult to be refurbished for its data object. It also difficult to map all locations of waste disposal legal in Lubuklinggau. Therefore, it neede fast an information systems, accurate and easy to be understood so that all locations of waste disposal legal can be know by the wider community. In addition, the management process was done by goverment, it can be coordinated by Department of Hygiene and Gardening in Lubuklinggau. In resolving of this issue, the writes tried use the development of technology application GIS (Geographic Information Systems) in order there were a mapping system location of the distribution waste disposal legal so that it’s easy for doing changes the data, provide the information and it also can be accessed by using mobile device. The result of this study was an application of Geographic Information Systems in mapping the location of waste disposal legal that consisted of main page, map page, detail of location waste disposal page, login admin page, home administrator page, and location processing page where for all menu provides complete information for the user.